A central role for G9a and EZH2 in the epigenetic silencing of cyclooxygenase-2 in idiopathic pulmonary fibrosis - Coward, William R.; Feghali-Bostwick, Carol A.; Jenkins, Gisli; Knox, Alan J.; Pang, Linhua (Federation of American Society of Experimental Biology, 2014)
Selective silencing of the cyclooxygenase-2 (COX-2) gene with the loss of the antifibrotic mediator PGE2 contributes to the fibrotic process in idiopathic pulmonary fibrosis (IPF). This study explored the role of G9a- and EZH2-mediated methylation of histone H3 lysine 9 (H3K9me3) and 27 (H3K27me3) in COX-2 silencing in IPF. Chromatin immunoprecipitation (ChIP) and Re-ChIP assays demonstrated marked increases in H3K9me3, H3K27me3 and DNA methylation, together with their respective modifying enzymes G9a, EZH2 and DNA methyltransferases (Dnmts) and respective binding proteins heterochromatin protein 1 (HP1), polycomb protein complex 1 (PRC1) and MeCP2, at the COX-2 promoter in lung fibroblasts from IPF patients (F-IPF) compared with fibroblasts from non-fibrotic lungs (F-NL). HP1, EZH2 and MeCP2 in turn were associated with additional repressive chromatin modifiers in F-IPF. G9a and EZH2 inhibitors and siRNAs and Dnmt1 inhibitor markedly reduced H3K9me3 (49-79%), H3K27me3 (44-81%) and DNA methylation (61-97%) at the COX-2 promoter. This was correlated with increased histone H3 and H4 acetylation, resulting in COX-2 mRNA and protein re-expression in F-IPF. Our results support a central role for G9a- and EZH2-mediated histone hypermethylation and a model of bidirectional, mutually reinforcing and interdependent crosstalk between histone hypermethylation and DNA methylation in COX-2 epigenetic silencing in IPF.